Human infections with neglected vector-borne pathogens in China: A systematic review - Yan-Qun Sun; Tao Wang; Yuan-Yuan Zhang; Tian-Le Che; Fan-Fei Meng; Ai-Ying Teng; Mei-Chen Liu; Ting-Ting Li; Bao-Gui Jiang; Qiang Xu; Chen-Long Lv; Jin-Jin Chen; et al. (Elsevier, 2022)
Summary: Background: Emerging vector-borne pathogens (VBPs) pose a continuous background threat to the global health. Knowledge of the occurrence, distributions and epidemiological characteristics of VBP are lacking in many countries. Outbreaks of novel VBP are of increasing global interest including those arising in China. Methods: A systematic review of published literature was undertaken to characterize the spectrum of VBPs causing human illness in China. We searched five databases for VBP-related articles in English and Chinese published between January 1980 and June 2021, that excluded those listed in the National Notifiable Diseases Surveillance System of China. The study is registered with PROSPERO, CRD42021259540. Findings: A total of 906 articles meeting the selection criteria were included in this study. A total of 44,809 human infections with 82 species of VBPs including 40 viruses, 33 bacteria (20 Rickettsiales bacteria, eight Spirochaetales bacteria, and five other bacteria) and nine parasites, were identified in China. Rickettsiales bacteria were the most common and widely distributed pathogens with 18,042 cases reported in 33 provinces by 347 reviewed articles, followed by Spirochaetales bacteria with 15,745 cases in 32 provinces (299 articles), viruses with 8455 cases in 30 provinces (139 articles), other bacteria with 2053 cases in 19 provinces (65 articles), parasites with 514 cases in 17 provinces (44 articles), and multiple pathogens with 3626 cases in 14 provinces (23 articles). Coxiella burnetii, Bartonella henselae and Rickettsia sibirica were the most frequently reported pathogens. A total of 18 new pathogens were reported in China during this period (these also represented their first identification globally). Based on 419 articles with clinical information, a meta-analysis revealed that flu-like illness was the most common manifestation among infections with VBPs. Interpretation: This review helps improve the understanding of VBPs in China, demonstrating the need to consider a wider surveillance of VBPs in many different settings, thus helping to inform future research and surveillance efforts. Funding: Natural Science Foundation of China.